Evaluating Decision Speed as a Measure of Public Procurement Performance in the European Single Market. Issue 13 (3rd October 2021) - Prier, Eric; McCue, Clifford P.; Csáki, Csaba
ABSTRACT: Public procurement across the European Union (EU) accounts for approximately 14% of GDP. The EU reports member states' procurement execution through the Single Market Scoreboard. One of these performance measures quantifies procurement decision speed, which assumes if member states reduce the time it takes to select vendors, there will be a reduction in transaction costs (increased efficiency). This research empirically evaluates procurement decision speed across a variety of government settings and procurement procedures to determine if decision speed, as defined by the Scoreboard, is a valid measure of performance. Findings suggest that decision speed as an efficiency performance measure lacks informational context; masks important underlying variation; and structurally omits the influence of important variables that contribute to variations in decision speed. Consequently, the utility of the Scoreboard measures of performance is called into question.